Analysis of labor consumption in Hungary in the last 5 years - Csipkés, Margit (International Journal of Engineering and Management Sciences, 2022)
The main idea of ​​my research was the statement of the President of the Hungarian Fruit and Vegetable Interprofessional Organization and Product Council (Ferenc Apáti), according to which the main obstacle to the future development of horticulture and the development plans of horticultural enterprises is capital shortfall factors). The employment of seasonal workers in the production of grapes and fruit and in horticultural farms is of the greatest importance. As a result, in my research, I examined the use of labor by those working in agriculture over the past 5 years. I reviewed how the coronavirus has affected the time spent by seasonal workers at work in the recent past. Since there are a lot of work phases in agriculture where there is a temporary use of labor, I considered it important to get around this topic better. As seasonal agricultural workers are often able to reach their agricultural jobs through travel and border crossings, government regulations (travel restrictions, border closures) have made it more difficult for these people to access jobs.